2019
DOI: 10.1177/1470412919841022
|View full text |Cite
|
Sign up to set email alerts
|

Catching the ghost: the digital gaze of motion capture

Abstract: Created with digital motion capture, or mocap, the virtual dances Ghostcatching and as.phyx.ia render movement abstracted from choreographic bodies. These depictions of gestural doubles or ‘ghosts’ trigger a sense of the uncanny rooted in mocap’s digital processes. Examining these material processes, this article argues that this digital optical uncanny precipitates from the intersubjective relationship of performer, technology, and spectator. Mocap interpolates living bodies into a technologized visual field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…With the advancement of motion capture technology, its use has become broader and more sophisticated. For example, in recent Hollywood films, motion capture technology has been used to create lifelike and expressive fantasy animal characters, delivering a deep visual experience for the audience [19], [20]. [21] also emphasizes that 3D animation technology is not just a visual tool but has become a medium capable of creating strong emotional engagement for the audience.…”
Section: Literature Review a Evolution Of 3d Animation And The Role O...mentioning
confidence: 99%
“…With the advancement of motion capture technology, its use has become broader and more sophisticated. For example, in recent Hollywood films, motion capture technology has been used to create lifelike and expressive fantasy animal characters, delivering a deep visual experience for the audience [19], [20]. [21] also emphasizes that 3D animation technology is not just a visual tool but has become a medium capable of creating strong emotional engagement for the audience.…”
Section: Literature Review a Evolution Of 3d Animation And The Role O...mentioning
confidence: 99%
“…Therefore, in the process of bodily expression, dancers need to pay attention to the details of the movements. Chang, V. et al explored dance and art performances based on digital motion capture technology and concluded that these forms are not conducive to the expression of individual artistic autonomy [9]. Li, Z. et al revealed the current situation of the application of new technology in dance teaching and found that there were many problems in the teething stage of technology and dance teaching.…”
Section: Introductionmentioning
confidence: 99%